Some Advances in Applications of Lattice Boltzmann Method for Complex Thermal Flows (Advances in Applied Mathematics and Mechanics, 2021)
Over the past two decades, there have been enormous advances in latticeBoltzmann (LB) numerical simulation and modelling. The lattice Boltzmannmethod has become a practical and promising tool for many fluid problems.A majority of recent studies have relied on numerical computations ofisothermal flows. However, much less efforts have been devoted to complexthermal flows, such as flows in porous media subjected to external magneticforce, flows with temperature-dependent properties. In this paper, an overviewis made based on some accomplishments in these numerical endeavours. Along withthe paper's sections, the state-of-the-art trend and the LBM advances in modellingand in computational aspects for specific classes of problems of major interestwill be fully touched on. Concluding remarks are given and the axis of our futurestudies will be traced.